IMPLEMENTASI-DISCOVERY LEARNING DALAM PEMBELAJARAN.DARING.PAI DI SMP WAHID HASYIM KOTA MALANG - Jamilatur Rosyidah; Abdul Jalil; Eko Setiawan (VICRATINA, 2021)
The-Discovery-learninggmodellis a learning model-that-isssapplied at the Wahid Hasyim Junior High School in Malang, the institution is one of the private schools located in a city. Many factors affect students, especially religion. So, teachers apply this kind of learning model so that all students can easily understand the material and apply it. The purpose of this research is to reveal a holistic-contextual phenomenon through collecting data from natural settings as a direct source with the researcher's own key instrument. This research is a qualitative approach, this type of research is a field research using a multi-site design. Sources of research data are PAI teachers, school principals, waka curriculum, documents. The implementation of the discovery learning model at Wahid Hasyim Middle School went well when the Pie teacher applied it in his learning. The supporting factors for the learning process are the high level of curiosity and curiosity of students in learning materials, the attitude of educators who are open in motivating students, especially parents, and adequate school facilities. The inhibiting factor is the ego of students in receiving lessons, sometimes they are also not ready.